The dynamics of the informal economy in West Africa: Case of Mali - (:unkn) unknown (My University, 2022)
All the economies of the world are made up of a more or less formal part and another more or less informal. The relative share of each of these parts depends on the level of economic and social development of the country, the more the economy and the society develop and modernize, the more the share of the informal economy is reduced.The informal economy has gradually become a fertile field of study that attracts the attention and interest of university researchers, development research centers, national governments and also international organizations.Like the other regions of Africa, all the studies show that the share of the informal economy is relatively large in West African countries, which prompted us to study the case by taking as an inventory the country of Mali.This work analyzes the spread and development of the informal economy in West Africa in general and its emergence in the country of Mali in particular, of which we will first present the general and economic situation of the country, then we will proceed to the description of the informal economy in Mali by the presentation of the figures, and this in order to be able to identify its share and its importance in the economy of the country, and to draw at the end the main conclusions of the said situation
Keywords: African Research